Vibration of mechanically-assembled 3D microstructures formed by compressive buckling. (March 2018) - Wang, Heling; Ning, Xin; Li, Haibo; Luan, Haiwen; Xue, Yeguang; Yu, Xinge; Fan, Zhichao; Li, Luming; Rogers, John A.; Zhang, Yihui; Huang, Yonggang
Highlights: Analytic solution of vibration modes and linear natural frequency of a buckled ribbon. Mode change as the static deflection amplitude of buckled ribbon increases. Scaling law of linear natural frequency for general, complex 3D structures. Reduced vibration nonlinearity as deflection amplitudes of 3D structures increase. Abstract: Micro-electromechanical systems (MEMS) that rely on structural vibrations have many important applications, ranging from oscillators and actuators, to energy harvesters and vehicles for measurement of mechanical properties. Conventional MEMS, however, mostly utilize two-dimensional (2D) vibrational modes, thereby imposing certain limitations that are not present in 3D designs (e.g., multi-directional energy harvesting). 3D vibrational micro-platforms assembled through the techniques of controlled compressive buckling are promising because of their complex 3D architectures and the ability to tune their vibrational behavior (e.g., natural frequencies and modes) by reversibly changing their dimensions by deforming their soft, elastomeric substrates. A clear understanding of such strain-dependent vibration behavior is essential for their practical applications. Here, we present a study on the linear and nonlinear vibration of such 3D mesostructures through analytical modeling, finite element analysis (FEA) and experiment. An analytical solution is obtained for the vibration mode and linear natural frequency of a buckled ribbon, indicating a mode change as the static deflection amplitude increases. The model also yields a scaling law for linear natural frequency that can be extended to general, complex 3D geometries, as validated by FEA and experiment. In the regime of nonlinear vibration, FEA suggests that an increase of amplitude of external loading represents an effective means to enhance the bandwidth. The results also uncover a reduced nonlinearity of vibration as the static deflection amplitude of the 3D structures increases. The developed analytical model can be used in the development of new 3D vibrational micro-platforms, for example, to enable simultaneous measurement of diverse mechanical properties (density, modulus, viscosity etc.) of thin films and biomaterials. Graphical abstract: Image, graphical abstract